Effects of Two Protein Hydrolysates Obtained From Chickpea (Cicer arietinum L.) and Spirulina platensis on Zea mays (L.) Plants - Ertani, Andrea; Nardi, Serenella; Francioso, Ornella; Sanchez-Cortes, Santiago; Foggia, Michele Di; Schiavon, Michela (Frontiers in Plant Science, 2019)
Two liquid protein hydrolysates obtained from chickpea (Cicer arietinum L.) (CA) and Spirulina platensis (SP) were analysed via FT-IR and SERS spectroscopy. Their hormone-like activities and contents in indole-3-acetic acid (IAA), isopentenyladenosine (IPA), nitrogen (N), carbon (C), sulphur (S), phenols, amino acids, and reducing sugars were determined. CA and SP showed different chemical compositions in N, C, sugars, amino acid and TP contents, which were generally higher in CA. The two products exhibited (IAA)-like and gibberellin (GA)-like activities and contained the hormones indole-3-acetic acid (IAA) and isopentenyladenosine (IPA). Specifically, CA held higher ( 3.6 fold) IAA-like activity than SP, while its GA-like activity was comparable to SP. The content in IAA was similar between hydrolysates, but CA contained 6 fold more IPA. CA and SP were further supplied at two different dosages (0.1 and 1 mL L-1) for two days to maize (Zea mays L.) plants grown in hydroponics. They positively influenced plant growth and accumulation of N-compounds (proteins, chlorophylls and phenols), with a more pronounced effect observed in plants treated with CA. Furthermore, they increased the activity of two enzymes, i.e. peroxidase and esterase, which are established markers for plant growth, differentiation and organogenesis-related processes. Peroxidase activity in particular, was enhanced by 1.6 and 2.3 fold in leaves and roots of CA-treated plants, respectively. Greater accumulation of macro (Ca, Mg and K) and micro (Cu, Zn) elements was also evident in plants supplied with these products. In conclusion, our data indicate that both CA and SP exert positive effects in maize plants. However, CA appeared to be more efficient than SP to improve plant nutrition and growth parameters in some respects, likely by virtue of its higher content in phytochemicals (hormones, phenols, amino acids, reducing sugars) that may act as signalling molecules, and more pronounced IAA-like activity.